2023
DOI: 10.3390/antiox12010208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Pomegranate Peel with Xylanase on Egg Quality and Antioxidant Parameters in Laying Hens

Abstract: Pomegranate contains bioactive compounds in all its parts. In this study, two levels of pomegranate peel byproduct (PPB) with or without the inclusion of xylanase enzyme were used to supplement laying hens’ diet, in a 2 × 2 full factorial design. A total of 48 Isa brown laying hens were fed the following experimental diets for 8 weeks: T1 (2.5% PPB); T2 (2.5% PPB and xylanase); T3 (5% PPB); T4 (5% PPB and xylanase). Eggs collected were analyzed for egg quality parameters. Moreover, egg yolks were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Olive byproducts contain high concentrations of phenolic compounds, which are bioactive metabolites derived from plant species [ 66 ]. It was assumed that the phenolic compounds found in olive leaf extract could be transferred to the tissues of broiler chickens and enrich the nutritional value of meat.…”
Section: Discussionmentioning
confidence: 99%
“…Olive byproducts contain high concentrations of phenolic compounds, which are bioactive metabolites derived from plant species [ 66 ]. It was assumed that the phenolic compounds found in olive leaf extract could be transferred to the tissues of broiler chickens and enrich the nutritional value of meat.…”
Section: Discussionmentioning
confidence: 99%
“…Literature about the deposition of total phenolic compounds in egg yolk is scarce. It has been shown that phenolic compounds found in poultry feed can be transferred and deposited in egg yolk [82,83], but the circumstances and the factors that are involved in phenolics' bioavailability and deposition in egg yolk are still under investigation. In the present study, T4 feed samples had similar TPC to T1, but TPC was more than 2.5-fold higher in T2 diet and almost 5-fold higher in T3 diet in comparison with T1.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are contrary to those reported by Lokaewmanee et al [9], who observed no significant difference in the specific gravity of quail eggs fed on dietary mango peels. Lioliopoulou et al [20] observed a significant (p < 0.05) effect on egg specific gravity on layer hens fed pomegranate peels.…”
Section: Specific Gravitymentioning
confidence: 96%